Impact of Pregnancy Induced Hypertension on Birth Weight of Newborn at Term - Arshad, Aleem; Pasha, Waseem; Khattak, Tariq Azam; Kiyani, Rizwan Bashir (Journal of Rawalpindi Medical College, 2025)
Background: To determine the birth weight of newborns at term born to mothers with pregnancy induced hypertension. Methods: In this cross sectional study birth weight of 124 newborns, of mothers with pregnancy induced hypertension were recorded within one hour of delivery Results: In 124 mothers, who fulfilled the inclusion criteria, the incidence of Pregnancy Induced Hypertension was 24.2 %. None of the patients had pre-eclampsia or eclampsia. The average birth weight among the total cases was 3.044 kg. The incidence of low birth weight babies among the pregnancy induced hypertensive pregnancies was 3.33%. The incidence of normal weight babies, among the pregnancies affected with Pregnancy Induced Hypertension was 96.66%. Conclusion: Pregnancy Induced Hypertension has no significant effect on birth weight of new born